Elite athletes and COVID-19 lockdown: Future health concerns for an entire sector - Paoli, A.; Musumeci, G. (Journal of Functional Morphology and Kinesiology, 2020)
In this editorial, we focused our attention on elite athletes during the COVID-19 lockdown. A high level of physical fitness is required by elite athletes irrespective of the specific type of sport. Generally speaking, elite athletes avoid long periods of rest during and at the end of the competitive season. Normally, elite athletes stop training or reduce training volume and intensity for a period that ranges from two weeks to a maximum of four weeks